The Pseudomonas Quinolone Signal (PQS): Not Just for Quorum Sensing Anymore - Lin, Jinshui; Cheng, Juanli; Wang, Yao; Shen, Xihui (Frontiers in Cellular and Infection Microbiology, 2018)
The Pseudomonas quinolone signal (PQS) has been studied primarily in the context of its role as a quorum-sensing signaling molecule. Recent data suggest, however, that this molecule may also function to mediate iron acquisition, cytotoxicity, outer-membrane vesicle biogenesis, or to exert host immune modulatory activities.